Portuguese validation of the Cognitive Emotion Regulation Questionnaire short version in youth: Validity, reliability and invariance across gender and age - Santos, A. (2022)
The Cognitive Emotion Regulation Questionnaire (CERQ) is a multidimensional measure widely used to access nine cognitive emotion regulation strategies. In this study, we examined the psychometric properties of the CERQ-Short Portuguese version. A sample of 1052 adolescents (aged 10-25 years old, 60.53% females) completed the CERQ-Short form, the Positive and Negative Affect Schedule, the Generalised Anxiety Disorder Scale, and the Patient Health Questionnaire. Confirmatory factor analyses showed that the nine latent dimensions of CERQ-Short provided an acceptable fit to the data. Measurement invariance (for gender and three age groups), reliability, and construct validity were adequate. The adaptative strategies were positively associated with higher positive affect, and maladaptive strategies with higher negative affect, symptoms of generalized anxiety, and depression. These results suggest that CERQ-Short is a valid and reliable measure for Portuguese-speaking samples. Moreover, CERQ-Short’s length makes it a cost-effective tool for both clinicians and researchers.